2022
DOI: 10.3389/fpubh.2022.878259
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Family-Centered Empowerment Model on Psychological Improvement of Patients With Myocardial Infarction: A Bayesian Multivariate Approach

Abstract: ObjectiveThere is a limited understanding of the impact of the family-centered empowerment model (FCEM) on the psychological symptoms in post-myocardial infarction (MI). This study aimed to evaluate the effectiveness of the FCEM on the psychological improvement of patients with MI.MethodsThe present study was a randomized controlled trial (RCT) where patients experienced a standard home cardiac rehabilitation (CR) or CR utilizing the FCEM approach. The empowerment of patients was estimated during nine assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
0
0
Order By: Relevance
“…Through the training of the FECM group, this study advocates the main caregivers to actively participate in the baby oil classroom, group meetings, bedside skills training, and other projects, to maximize the rights of the main caregivers, cultivate the care skills of the main caregivers, improve the care ability of the main caregivers, and provide a prerequisite for a smooth transition to home care after discharge and improve the quality of life of premature infants. The results are similar to those of Raei et al ( 16 ). At the same time, primary caregivers are not only providers of care services but also excavators of the potential abilities of preterm infants, which can significantly optimize the health outcomes of preterm infants ( 17 ).…”
Section: Discussionsupporting
confidence: 92%
“…Through the training of the FECM group, this study advocates the main caregivers to actively participate in the baby oil classroom, group meetings, bedside skills training, and other projects, to maximize the rights of the main caregivers, cultivate the care skills of the main caregivers, improve the care ability of the main caregivers, and provide a prerequisite for a smooth transition to home care after discharge and improve the quality of life of premature infants. The results are similar to those of Raei et al ( 16 ). At the same time, primary caregivers are not only providers of care services but also excavators of the potential abilities of preterm infants, which can significantly optimize the health outcomes of preterm infants ( 17 ).…”
Section: Discussionsupporting
confidence: 92%
“…One of the main factors of health promotion is health literacy, which includes any activity aimed at increasing health awareness, and its purpose is to promote health and prevent disease and illnesses [71]. In addition, Raei, et al [72], while investigating the effectiveness of the family-centered empowerment model in following the treatment of post-PCI patients, reported that improving family health literacy along with the patient is correlated with reducing stress, improving physical activity and health-related quality of life [72]. Duncan S, et al concluded that family-based approaches that target caregivers and patients and pay attention to the structural and environmental conditions in which families live could be the most effective approach to promote cardiovascular health at three levels of prevention [73].…”
Section: Discussionmentioning
confidence: 99%